Passive drag reduction using full-body swimsuits: the role of body position - Cortesi, M.; Fantozzi, S.; Di Michele, R.; Zamparo, P.; Gatta, G. (The Journal of Strength and Conditioning Research, 2014)
This study aimed to analyze whether using full-body swimsuits affects the swimmer's body alignment and to what extent changes in the body position are responsible of the passive drag (Dp) reduction experienced by the swimmers when using these swimsuits. Fourteen swimmers performed 20-m towing trials using a full-body synthetic rubber swimsuit, a full-body textile swimsuit, a traditional brief swimsuit, and a traditional brief swimsuit with a pull buoy. In all trials, the speed-specific drag (k = Dp per v2), the trunk incline (TI), and the lower limbs incline (LI) were determined. In comparison with both conditions in which a full-body swimsuit was not used, k was significantly lower when using the rubber swimsuit (-8.4 and -12.2% vs. the brief swimsuit with and without pull bouy, respectively), and the textile swimsuit (-6.9 and -10.8% vs. the brief swimsuit with and without pull bouy, respectively). No differences in TI were observed among conditions, whereas LI was significantly higher when using the rubber swimsuit or the brief swimsuit with pull buoy than when using the traditional brief swimsuit. A linear mixed model showed that k can be reduced by increasing LI (that is lifting the lower limbs), by decreasing TI (that is keeping the trunk more horizontal), and by using either the rubber or textile full-body swimsuit rather than the traditional brief swimsuit. In conclusion, full-body swimsuits involve a reduction of a swimmer's passive drag caused by intrinsic properties related to the "material composition" of the swimsuits and also influenced by changes in the swimmer's body position.